Osteogenic Differentiation Potential of Equine Dental Pulp vs. Periodontal Ligament Stem Cells: A Comparative In Vitro Study - Purwaningrum, Medania; Haryanto, Aris; Kayanaveda, Yohanna; Sawangmake, Chenphop (Universitas Airlangga, 2025)
Equine mesenchymal stem cells (MSCs) are promising for bone tissue engineering (BTE) because of their capabilities of differentiating into osteoblasts. Cell therapy using equine MSCs has been introduced. Recently, dental-derived MSCs have gained significant attention due to their capabilities and ease of collection with minimally invasive collection methods. Dental stem cells show high plasticity, accessibility, and applicability for regenerative medicine and are thus considered alternative sources of MSCs. This study evaluated the characterization, osteogenic differentiation potential, and migration assay of equine dental pulp stem cells (eDPSCs) as compared with equine periodontal ligament stem cells (ePDLSCs). Equine dental stem cells from eDPSCs and ePDLSCs (n = 4) were isolated and expanded to passage 3. The morphology, colony-forming capability, cell proliferation assay, stemness and surface markers, trilineage differentiation potential, and migration assay were investigated in vitro. Both eDPSCs and ePDLSCs exhibited a fibroblast-like morphology; showed a colony-forming capability; were able to proliferate based on the results of the cell proliferation assay; expressed stemness and surface markers (NANOG, CD29, CD44, CD90, CD18); maintained the ability to differentiate into osteocytes, chondrocytes, and adipocytes and demonstrated migration capacity based on the migration assay. Surprisingly, ePDLSCs showed significant differences in matrix mineralization, quantification of Alizarin Red staining by cetylpyridinium chloride, and mRNA expression of the osteogenic marker RUNX2. ePDLSCs and eDPSCs may be better alternative MSCs than dental stem cells for the further design of therapeutic regimens for BTE and wound-healing therapy.